Enhancing the Activity of the DLPFC with tDCS Alters Risk Preference without Changing Interpersonal Trust - Zheng, Haoli; Wang, Siqi; Guo, Wenmin; Chen, Shu; Luo, Jun; Ye, Hang; Huang, Daqiang (Frontiers in Neuroscience, 2017)
Interpersonal trust plays an essential role in economic interactions and social development. Extensive behavioral experiments have examined the nature of trust, particularly the question of whether trusting decisions are connected to risk preferences or risk attitudes. Various laboratory observations have been reported regarding the difference between trust and risk, and neural imaging studies have demonstrated that the right dorsolateral prefrontal cortex (rDLPFC) is more activated when individuals decide to trust other human beings compared with individuals decide to invest in a non-social risk condition. Moreover, the rDLPFC has been found to exhibit an intimate relationship with risk preference in previous neuroscience studies. However, the causal relationship between the rDLPFC and trust has rarely been revealed. Whether modulating the excitability of the rDLPFC, which shares roles in both trust and risk decisions, alters the trust or risk preference of participants remains unknown. In the present study, we aimed to provide evidence of a direct link between the neural and behavioral results through the application of transcranial direct current stimulation (tDCS) over the rDLPFC. We found that activating the rDLPFC altered the risk preferences of our participants, whereas no such significant effect over interpersonal trust was observed. Our findings indicate that enhancing the excitability of the rDLPFC using tDCS leads to more conservative decision-makings in a risk game, and this effect is specific to non-social risk rather than social-related trust.